Epidemiology of injuries in professional ice hockey: a prospective study over seven years - Gregory Ornon; Jean-Luc Ziltener; Daniel Fritschy; Jacques Menetrey (Journal of Experimental Orthopaedics, 2020)
Abstract Background Ice hockey injuries epidemiology is still poorly understood and very few studies are focused on it, especially about professional players. Methods Our prospective study collected all injuries occurring on ice during practice and games over 7 years (2006–2013) in a professional hockey team playing in the 1st division championship in Switzerland. Results During the 7 seasons, we recorded a total of 525 injuries and 190 injuries with time loss (TL). Mean injuries incidence was 5.93 (95% CI 5.28 to 6.27) injuries/1000 h/player and with time loss 2.14 (95% CI 1.79 to 2.39) injuries/1000 h/player. The lower limb was the most affected part of the body, with a total of 40.4% of all injuries, mostly knee Medial Collateral Ligament tear and muscle adductors/abdominal sprain. For the upper limb, shoulder was the most affected joint with mostly acromioclavicular sprain and shoulder dislocation. Forwards had a significant (p < 0.05) higher risk than defensemen for knee Medial Collateral Ligament (MCL) tear. There was no significant difference in the concussion risk between forwards and defensemen, but defensemen had a significant higher risk (p < 0.05) to have a more severe concussion. Conclusion This study provides a better understanding about professional ice hockey epidemiology, which is still insufficiently researched and understood. We also found some significant risk factors, being a forward for knee MCL tear, being a defensemen for concussion severity. Concussion program prevention seems to be effective but it is crucial to continue the follow up of concussion on long term and expand the surveillance system to all the League.